A sustainable development assessment of Indonesia's state banks financing for the industrial and non-industrial sector. (3rd July 2022) - Nandiwardhana, Aditya Pratama; Cudjoe, Dan; Permana, Dudi
ABSTRACT: Global warming has adversely affected the environment and other living aspects. In addition to being a result of increased industrial and non-industrial sector activity, state bank financing aimed at both sectors can provide positive contributions to sustainable development index while also providing a negative impact. This paper results revealed that although state bank financing provides a proportion of approximately 15% and 5% for all sectors with no long-term relationship, results from IRF formative analysis can discover which sector financing still lacks sustainable development behavior. Furthermore, IRF reflective analysis in this study completes the explanation that the index can reveal financing that is ready to support sustainable development. Finally, this research findings show that sustainable development policies and regulations are not the sole determinants to implement sustainable strategy initiatives. However, access to institutional financing, sufficient short-term financing, and technology availability will encourage Indonesia's sustainable development financing strategy.